FAUNISTIC ANALYSIS OF GROUND DIGGER WASPS OF (HYMENOPTERA: SPHECIDAE) FAMILY IN THE FERGANA VALLEY (American Journal of Technology and Applied Sciences, 2025)
The article presents information about the location, distribution, bioecology of species Palmodes melanarius, Podalonia affinis, P.ebenina, Sceliphron madraspatanum F, Sphex funerarius.